Effects of Feeding Increasing Standardized Ileal Digestible Lysine on Growth Performance of 26- to 300-lb PIC Line 800-Sired Pigs - Katelyn N. Gaffield; Mike D. Tokach; Jason C. Woodworth; Joel M. DeRouchey; Robert D. Goodband; Jordan T. Gebhardt; Carine M. Vier; Matthew Spindler; Uislei Orlando; Luis Zargoza; Ning Lu; Wayne Cast; et al. (Kansas Agricultural Experiment Station Research Reports, 2022)
The objective of this study was to evaluate the growth performance and economic returns of PIC 800 × 1050 pigs fed increasing SID Lys from approximately 26 to 300 lb. Pens of pigs were blocked by BW and randomly assigned to 1 of 5 dietary treatments in a randomized complete block design with 26 pigs per pen and 16 pens per treatment. Pens were provided 1 of 5 dietary treatments with increasing SID Lys at 85, 93, 100, 107, and 115% of current PIC recommendations within 6 different phases. Two base diets containing low Lys and high Lys were blended to meet target SID Lys levels for each treatment diet within phase. For the overall experimental period (d 0 to 143), feeding increasing SID Lys improved (linear,P≤ 0.007) ADG and F/G, but did not impact ADFI (P>0.10). For carcass characteristics, a tendency (linear,P= 0.067) for increased HCW of pigs that were provided increasing SID Lys was observed. However, there was no evidence for differences (P>0.10) across treatments in carcass yield, backfat depth, loin depth, or carcass lean percentage. Increasing SID Lys of the diets increased (linear,P<0.001) feed cost and feed cost per lb of gain. There was no evidence of difference (P>0.10) in revenue for either ingredient price scenario, thus, feeding increasing levels of SID Lys reduced (linear,P<0.001) income over feed cost (IOFC) in both scenarios. The linear model (LM) served as the best fit for both growth and economic parameters. The LM model predicted maximum ADG and minimal F/G at levels greater than 115% of PIC’s current SID Lys recommendations. For IOFC, the LM model predicted maximum profitability at or below 85% of PIC’s current Lys recommendations. In conclusion, the optimal SID Lys level for PIC 800 × 1050 pigs from 26- to 300-lb depends upon the response criteria, with growth performance maximized at levels at or above 115% of PIC’s recommendation for SID Lys; however, economic responses were maximized at or below 85% of PIC’s current SID Lys recommendations.
Keywords: amino acid; grow-finish pig; lysine; requirement